Plasmonics for Telecommunications Applications - F. Carvalho, William O. (Sensors (Basel), 2020)
Plasmonic materials, when properly illuminated with visible or near-infrared wavelengths, exhibit unique and interesting features that can be exploited for tailoring and tuning the light radiation and propagation properties at nanoscale dimensions. A variety of plasmonic heterostructures have been demonstrated for optical-signal filtering, transmission, detection, transportation, and modulation. In this review, state-of-the-art plasmonic structures used for telecommunications applications are summarized. In doing so, we discuss their distinctive roles on multiple approaches including beam steering, guiding, filtering, modulation, switching, and detection, which are all of prime importance for the development of the sixth generation (6G) cellular networks.